Osteoporosis, arterial calcification, and kidney stone disease: modern anti-aging modalities (literature review) - O.I. Nishkumay; Mike K.S. Chan; Yu.I. Nalapko; H.V. Mostbauer; O.O. Alekseenko; O.D. Nikitin; I.A. Kordubailo (Bolʹ, Sustavy, Pozvonočnik, 2023)
Background. The problem of osteoporosis as well as a cardiovascular disease remains one of the leading in the statistics of morbidity and mortality due to the aging of the population throughout the world. Recent publications accentuate the new viewpoint to an association of this statistic with the mechanism of the “calcium paradox”. These processes can have common risk factors when endothelial cells of different organs have been modified to osteoblasts-like bone cells and become intensive capture calcium crystals. This pathological process results in bone and vessel fragility and nephrocalcinosis. This pathogenesis is complex and common but not fully understood mechanisms. The purpose was to analyze the current literature data on reasons and molecular mechanisms of bone remodeling and vascular calcification according to a literature review over the past 5 years. Materials and methods. An analytical review of literature data was conducted using the information analysis of Medline (PubMed), Web of Science and Scopus databases, Google Scholar, and the Cochrane Central Register of Controlled Trials (CENTRAL) for 2018–2023 using the keywords “osteoporosis”, “atherosclerosis”, “vascular calcification”, “stem cells”, “exosomes”, “kidney stones diseases”. Results. The literature analysis underlines the multiplay pathogenetic mechanisms as common lifestyle risk factors (calcium and vitamin D, K2 deficiency smoking), as an osteosarcopenia, immunoaging, and stem cell senescence. Conclusions. In order to solve the problem prevention of the “calcium paradox”, it is necessary to access the correction of multiple mechanisms: calcium and vitamin D, K2 deficiency, reasons causing secondary hyperparathyroidism, falling, osteosarcopenia, immunoaging, and senescence of stem cells, microRNA and exosomes. A new understanding of the problem opens up opportunities for influencing all the known links and new perspectives of treatment.